Modeling economic growth in contemporary Hong Kong - Fung, Michael K.; Sergi, Bruno S. (Entrepreneurship and global economic growth., 2021)
Serving up fresh insights on Hong Kong's economic growth, this book investigates issues such as housing, immigration, monetary and financial systems, the business environment, and international trade and finance to provide a coherent and comprehensive overview of Hong Kong's position in the global economy. Exploring these interrelated topics chapter-by-chapter, the authors cover contemporary macroeconomic topics such as government policies supporting structural changes of the Hong Kong economy challenges to the pillars of Hong Kong's economic growth, factors determining the success and failure of emerging sectors, the impacts of the linked exchange rate system on the financial and monetary markets, the tightening integration between the Hong Kong and Mainland China economies, Hong Kong's real estate market and its socio-economic impact, regional competition, and the operation and contribution of Mainland Chinese enterprises in Hong Kong. With broad application across several courses, this book is appealing reading to researchers in the fields of economic policy, economic growth, financial modelling, and more.